Development of Loop-Mediated Isothermal Amplification (LAMP) Assay for In-Field Detection of American Plum Line Pattern Virus - Matić, Slavica; Myrta, Arben (Viruses, 2024)
American plum line pattern virus (APLPV) is the most infrequently reported Ilarvirus infecting stone fruit trees and is of sufficient severity to be classified as an EPPO quarantine A1 pathogen. In late spring, yellow line pattern symptoms were observed on leaves in a few flowering cherries (Prunus serrulata Lindl.) grown in a public garden in Northwest Italy. RNA extracts from twenty flowering cherries were submitted to Ilarvirus multiplex and APLPV-specific RT-PCR assays already reported or developed in this study. One flowering cherry (T22) with mixed prunus necrotic ringspot virus (PNRSV) and prune dwarf virus (PDV) infection also showed infection with APLPV. Blastn analysis of PCR products of the full coat protein (CP) and movement protein (MP) genes obtained from flowering cherry T22 showed 98.23% and 98.34% nucleotide identity with reference APLPV isolate NC_003453.1 from the USA. Then, a LAMP-specific assay was designed to facilitate the fast and low-cost identification of this virus either in the laboratory or directly in the field. The developed assay allowed not only the confirmation of APLPV (PSer22IT isolate) infection in the T22 flowering cherry but also the identification of APLPV in an asymptomatic flowering cherry tree (TL1). The LAMP assay successfully worked with crude flowering cherry extracts, obtained after manually shaking a single plant extract in the ELISA extraction buffer for 3–5 min. The developed rapid, specific and economic LAMP assay was able to detect APLPV using crude plant extracts rather that RNA preparation in less than 20 min, making it suitable for in-field detection. Moreover, the LAMP assay proved to be more sensitive in APLPV detection in flowering cherry compared to the specific one-step RT-PCR assay. The new LAMP assay will permit the estimation of APLPV geographic spread in the territory, paying particular attention to surrounding gardens and propagated flowering cherries in ornamental nurseries.